Gaviota Cocinera (Larus dominicanus) atacando a un Pato Maicero (Anas spinicauda) - Roesler, Ignacio; Punta Fernández, Diego; Hernández, Pablo (Nuestras Aves, 2013)
Este artículo no cuenta con un resumen.